Reforming Public Sector Bureaucracy: A Systematic Literature Review of New Public Management in Indonesia - Nikki Prafitri; Arenawati; Ni Made Ayu Puspa Karini; Najla Assyifa Zahrani (Indonesian Journal of Social Science Research, 2025)
New Public Management (NPM) is a model that applies business styles to the public sector with the aim of increasing effectiveness and efficiency. The implementation of NPM based on literature studies is most widely applied in developed countries. The adoption of NPM is demonstrated by the implementation of performance-based and measurable programs or work. Indonesia has also adopted the NPM model in several areas, although there are gaps in analysis. This is because there are still limited specific case studies that reflect the implementation of the NPM model in Indonesia. This research method uses systematic literature review. The primary data source was the Scopus database, where a search was conducted using the keywords "New Public Management" and "Indonesia" in the document titles. The search results identified 30 relevant documents. The findings of this study are that research related to new public management in Indonesia shows less significant developments. The ineffectiveness of NPM adoption in public sector bureaucratic reform causes this model to be underdeveloped in its research studies. The factors that cause it are the dominance of traditional bureaucratic practices, the lack of strategic management to implement business styles in the public sector, changes towards the adoption of NPM are not accompanied by changes in the bureaucratic culture of the government apparatus, rigid and inflexible management, rigid budgeting system, lack of competition and innovation as well as dominant culture and political characteristics.